Synthesis, characterization, and photophysical properties of novel 9‑phenyl-9-phosphafluorene oxide derivatives - Shuxian Qiu; Duan Dong; Jiahui Li; Huiting Wen; Jinpeng Li; Yu Yang; Shengxian Zhai; Xingyuan Gao (Beilstein Journal of Organic Chemistry)
A novel series of D−A−D-type 9-phenyl-9-phosphafluorene oxide (PhFlOP) derivatives was prepared and is reported herein. The synthetic protocol involved 5 steps from commercially available 2-bromo-4-fluoro-1-nitrobenzene, featuring a noble-metal-free system, mild reaction conditions, and a good yield, especially for the final Cs2CO3-facilitated nucleophilic substitution (77–91% yield). The characterization data obtained from IR and NMR spectroscopy (1H, 13C, 19F, and 31P) as well as HRMS spectrometry were in full agreement with the expected structures, and single-crystal X-ray diffraction analysis was conducted to confirm the structure of compound 7-H. Moreover, the photophysical properties of these PhFlOP derivatives were determined by UV–vis absorption and photoluminescence studies, revealing that their photophysical behavior can be affected by the different substituents in the donor carbazole group.